Neurobiological Mechanisms Underlying the Therapeutic Effects of Physical Exercise in Autism Spectrum Disorder: A Narrative Review - Kuś, Justyna; Białowąs, Patrycja; Zięba, Natalia; Czapiński, Olgierd; Brodowska, Anna; Tomicka, Ewa; Knapik, Anna; Stadnicka , Olga; Ciesielski, Maciej; Pysiewicz, Mateusz (Quality in Sport, 2026)
Background. Autism Spectrum Disorder (ASD) is a heterogeneous neurodevelopmental condition characterized by impairments in social communication and the presence of restricted and repetitive behaviors. Increasing evidence suggests that structured physical exercise may serve as a supportive therapeutic approach. However, although exercise has been shown to improve both core symptoms and associated difficulties in ASD, the underlying biological mechanisms remain poorly understood. Aim. This review aims to summarize current evidence on the neurobiological mechanisms that may underlie the beneficial effects of physical exercise in individuals with Autism Spectrum Disorder. Material and methods. A narrative review of the literature was performed, focusing on studies exploring the interaction between physical exercise and neurobiological processes relevant to ASD. Studies were identified through databases such as PubMed and Scopus. Both clinical and preclinical studies were included to capture mechanistic insights related to brain function and structure. Results. Physical exercise modulate ASD related mechanisms involving immune regulation, gut-brain communication, synaptic plasticity, and hormonal responses. Current evidence points to changes in microglial activation, cytokine profiles, and gut microbiota composition, although mechanistic data remain largely preclinical. Conclusions. Structured physical exercise represents a promising complementary strategy in ASD, with potential benefits mediated through multiple neurobiological pathways. A better understanding of these mechanisms may support the development of targeted and individualized exercise based interventions tailored to the diverse needs of individuals with ASD.